IDENTIFIKASI KANDUNGAN PESTISIDA PADA SAYURAN ORGANIK DI PASAR MODERN - metty metty; Angelina Swaninda (Universitas Respati Yogyakarta, 2016)
Consumers need to know the certainty of the products in modern markets is pesticide-free organic vegetables and physical characteristics. Thus the researchers want to know the use of pesticides on organic vegetables in the modern market in Yogyakarta. This research is a survey or observational descriptive approach. Identification of pesticides is done in laboratory using thin layer chromatography test. The samples were randomly sampling. The sample was organic tomatoes from two modern markets (A and B) in Yogyakarta. Physical characteristics of the organic samples purchased two modern markets are nice and bright colors. Packaging is using stirioform and plastic. However, only one a modern market that has a certification logo. Two samples (A and B) do not include expired date on the label. The results of the test thin layer chromatography (pictures 5 and 6) in both samples showed no spots are the same as standard.Conclusions: Physical characteristics and packaging of samples A and B are good. Both samples have not included an expired date on the package. Only sample A which has organic certification logo. The test results pesticides by using Thin Layer Chromatography is negative in both samples Keywords: pesticides, organic vegetables, modern Markets